Below the disappearing marshes of an urban estuary: historic nitrogen trends and soil structure. Issue 4 (1st June 2014) - Wigand, Cathleen; Roman, Charles T.; Davey, Earl; Stolt, Mark; Johnson, Roxanne; Hanson, Alana; Watson, Elizabeth B.; Moran, S. Bradley; Cahoon, Donald R.; Lynch, James C.; Rafferty, Patricia
Abstract : Marshes in the urban Jamaica Bay Estuary, New York, USA are disappearing at an average rate of 13 ha/yr, and multiple stressors (e.g., wastewater inputs, dredging activities, groundwater removal, and global warming) may be contributing to marsh losses. Among these stressors, wastewater nutrients are suspected to be an important contributing cause of marsh deterioration. We used census data, radiometric dating, stable nitrogen isotopes, and soil surveys to examine the temporal relationships between human population growth and soil nitrogen; and we evaluated soil structure with computer‐aided tomography, surface elevation and sediment accretion trends, carbon dioxide emissions, and soil shear strength to examine differences among disappearing (Black Bank and Big Egg) and stable marshes (JoCo). Radiometric dating and nitrogen isotope analyses suggested a rapid increase in human wastewater nutrients beginning in the late 1840s, and a tapering off beginning in the 1930s when wastewater treatment plants (WWTPs) were first installed. Current WWTPs nutrient loads to Jamaica Bay are approximately 13 995 kg N/d and 2767 kg P/d. At Black Bank, the biomass and abundance of roots and rhizomes and percentage of organic matter on soil were significantly lower, rhizomes larger in diameter, carbon dioxide emission rates and peat particle density significantly greater, and soil strength significantly lower compared to the stable JoCo Marsh, suggesting Black Bank has elevated decomposition rates, more decomposed peat, and highly waterlogged peat. Despite these differences, the rates of accretion and surface elevation change were similar for both marshes, and the rates of elevation change approximated the long term relative rate of sea level rise estimated from tide gauge data at nearby Sandy Hook, New Jersey. We hypothesize that Black Bank marsh kept pace with sea level rise by the accretion of material on the marsh surface, and the maintenance of soil volume through production of larger diameter rhizomes and swelling (dilation) of waterlogged peat. JoCo Marsh kept pace with sea‐level rise through surface accretion and soil organic matter accumulation. Understanding the effects of multiple stressors, including nutrient enrichment, on soil structure, organic matter accumulation, and elevation change will better inform management decisions aimed at maintaining and restoring coastal marshes.